Dual-chamber cardiac pacing short-term effect on left and right atria morphometric parameters and function. (4th February 2022) - Viezelis, M; Neverauskaite-Piliponiene, G; Marcinkeviciene, A; Teleisyte, E; Kazakevicius, T; Zabiela, V; Kviesulaitis, V; Sileikis, V; Puodziukynas, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. Dual-chamber pacemaker implantation is a standard interventional treatment strategy for symptomatic sinus syndrome (SSS) or advanced atrioventricular block (AVB). It is already known that right ventricular pacing might have detrimental effects on cardiac function. However, knowledge about atrial pacing effect on left (LA) and right (RA) atria function is still lacking. Purpose. To assess the impact atrial pacing on left and right atria morphologic and functional parameters in patients after dual-chamber pacemaker implantation. Methods. We conducted a prospective study that included patients who received a dual-chamber pacemaker for an indication of AVB or SSS. A base rate of 40 bpm and no rate response in case of clear AVB indication or a base rate of 60 bpm and rate response if indication was SSS were chosen. A transthoracic echocardiography was done the next day after pacemaker implantation and after 1 and 3 months. To remove the impact of right ventricular pacing, patients with high VP percentage (>40%) were excluded from analysis. Patients were divided into two groups – group A with high AP (>50%), and group B – low AP (<50%). LA expansion fraction reflecting reservoir function, emptying - reflecting conduit, and active emptying reflecting "atrial kick" were analysed. To compare means the Mann Whitney U test, and for categorical variables – X² test were used. Results: A total of n = 78 patients underwent dual-chamber implantation and signed informed consent. Due to significant structural heart disease or reduced ejection fraction (<50%) 7 patients were excluded from further analysis. Out of those, n = 21 were excluded due to a high VP percentage. Group A consisted of n = 26 and group B of – n = 24 patients. Average AP in group A was 63, 5% and 68, 3% at 1 and 3 months and 5, 6% and 7, 2% in group B respectively. The mean age (group A 74, 5 SD 8, 6 years vs group B 78, 1 SD 8, 0 years, p = 0, 266), gender distribution (group A males 45, 5% vs group B 48, 4%, p = 0, 774), and mean BMI (group A 26, 4 SD 4, 8 kg/m2 vs group B 29, 5 SD 3, 7 kg/m2, p = 0, 202) did not differ significantly between the two groups. The mean left ventricular end diastolic diameter (LVEDD) and indexed LVEDD were not significantly different at baseline and did not change during the follow up period. The baseline LA and RA morphometric and functional parameters presented was not different at baseline between the two groups. The change in LA and RA functional parameters presented in figures. A tendency for a lower LA expansion fraction, active emptying fraction and LA ejection fraction were observed in group A. The trend was contant during 1 and 3 month follow-up periods. RA morphometric parameters did not change significantly between the two groups.  Conclusion: Impaired LA function in a higher percentage of atrial pacing is seen early after pacemaker implantation and could progress over time. Though, even longer observational period is needed.